2015
DOI: 10.1083/jcb.201504057
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 is intercellularly transmitted across axon terminals

Abstract: A protein complementation assay quantifying TDP-43 oligomerization in living neurons shows microvesicular and bidirectional synaptic transmission of TDP-43 and TDP-43 seeding activity in human ALS postmortem brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
272
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(302 citation statements)
references
References 46 publications
13
272
1
2
Order By: Relevance
“…23 It is likely that this mode of uptake is not specific to TDP-43 but to protein aggregates in general. 24,25 Similarly, both conditioned media containing TDP-43 from cultured cells, and homogenates from ALS patient brains, have been shown to interact with cell produced TDP-43 using a split luciferase reporter 11 and transduced TDP-43 aggregates from brain material has been shown to increase cell produced TDP-43 aggregation via western blot. 8,9 It is interesting to note that the transmission rates are low in these experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 It is likely that this mode of uptake is not specific to TDP-43 but to protein aggregates in general. 24,25 Similarly, both conditioned media containing TDP-43 from cultured cells, and homogenates from ALS patient brains, have been shown to interact with cell produced TDP-43 using a split luciferase reporter 11 and transduced TDP-43 aggregates from brain material has been shown to increase cell produced TDP-43 aggregation via western blot. 8,9 It is interesting to note that the transmission rates are low in these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…10 An additional study presented evidence to suggest that TDP-43 can transfer between HEK293 cells and primary cortical mouse neurons and interact with endogenous TDP-43 in recipient cells. 11 More recently, it was observed that TDP-43 fibrils formed from short C-terminal derived peptides triggered the seeddependent aggregation of wild type TDP-43 (TDP-43 WT ) or TDP-43 lacking a nuclear localization signal in SH-SY5Y cells resulting in different peptides sequences of TDP-43 producing fibrils with distinct biochemical properties reminiscent of prion strains. 12 Recently a novel method for quantifying protein inclusions was described.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study provides evidence for a primarily microvesicular intercellular spread of TDP-43 aggregates [203], and both neuronal and astroglial MVs have been implicated in the propagation of pathogenic misfolded SOD1. In vitro, motor neuron NSC-34 cells overexpressing wild type and mutant SOD1 secreted this protein via exosomes [204].…”
Section: Microglia May Drive Als Pathophysiologymentioning
confidence: 99%
“…By monitoring the levels of TDP-43 oligomers in vitro, TDP-43 has been found to communicate through the axon in the cell by synaptic and microencapsulated uptake [10] . With the help of nuclear magnetic resonance, simulation and microscopy, a sub-region has been found cooperatively but transiently to be folded into an a-Helical form that mediates TDP-43 phase separation [11] .…”
Section: Normal Tdp-43 and Its Functionmentioning
confidence: 99%